Topics in Cryptology - CT-RSA 2023 Cryptographers' Track at the RSA Conference 2023, San Francisco, CA, USA, April 24-27, 2023, Proceedings - Rosulek, Mike. (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book constitutes the refereed proceedings of the Cryptographer's Track at the RSA Conference 2023, CT-RSA 2023, held in San Francisco, CA, USA, in April 2023. The 26 full papers presented in this volume were carefully reviewed and selected from 76 submissions. The conference presents papers on subjects such as Cryptographic Implementations, Quantum Cryptanalysis, Advanced Public-Key Encryption, Tools for Privacy-Enhancing Technologies, Symmetric Cryptanalysis, Multiparty Protocols, Digital Signatures, Fault Attacks and Side Channels, Heuristic Approaches, Symmetric-Key Constructions, and Key Agreement.
Cryptographic Implementations -- Quantum Cryptanalysis -- Advanced Public-Key Encryption -- Tools for Privacy-Enhancing Technologies -- Symmetric Cryptanalysis -- Multiparty Protocols -- Digital Signatures -- Fault Attacks and Side Channels -- Heuristic Approaches -- Symmetric-Key Constructions -- Key Agreement.
Keywords: Cryptography; Data encryption (Computer science).; Cryptology